PENGARUH KARAKTER SPIRITUAL TERHADAP PRODUKTIVITAS SANTRI - Devi Maudiani; Ismaulina Ismaulina (Jurnal Ekonomi Syariah, Akuntansi dan Perbankan (JESKaPe), 2021)
This study aims to determine whether there is an effect of spiritual character on the productivity of students in the Bank Indonesia Islamic Boarding School Economic Independence Development Program at the Darul 'Ulum Al-Munawwarah Islamic Boarding School, Lhok Mon Puteh / Blang Pohroh, Cunda, Lhokseumawe City. This study uses a quantitative method with an associative approach. Data collection was carried out by distributing questionnaires with a sample of 25 respondents. To analyze the data using an analysis tool, namely SPSS version 22. The method of analysis used validity and reliability tests, normality test, simple linear regression test and hypothesis testing. The results showed that the t-test results of the spiritual character variable (x) had a positive effect on the productivity of the students (y) as evidenced by the t-count value greater than the t-table with a significance that was smaller than the determined significance. Economic Independence Development Program of the Bank Indonesia Islamic Boarding School at the Darul 'Ulum Al-Munawwarah Islamic Boarding School in Lhok Mon Puteh / Blang Pohroh, Cunda, Lhokseumawe City..